Social Cognitive Theory Test: Role of Anxiety in getting Professional Sanction in Professionalism and Auditor Independence - Francisca Reni Retno Anggraini; Zaki Baridwan; Suwardjono Suwardjono; Hardo Basuki (The Indonesian Journal of Accounting Research, 2017)
Abstract: Scandals in auditing have deteriorated the credibility of the accounting profession. The low law enforcement and concentrated ownership structure in Indonesia (La Porta et al., 1999; Siregar, 2006) has led to lower auditor independence. This study uses social cognitive theory in modeling. Based on social cognitive theory, law enforcement influences auditor’s concern to professional sanction. Then, the concern to professional sanction is cognitive which influence auditor's independence. The objectives of this research are to examine the effect of work context to the level of auditor’s concern to professional sanction, the role of auditor’s concern to professional sanction to his or her professionalism and independence. Based on scenario-based surveys in Jakarta, Surabaya, Semarang, Denpasar, Yogyakarta, we received 186 usable questionnaires (83 questionnaires from auditors working in non-big four accounting firms and 103 questionnaires from auditors who work in big four firms). This study uses multiple regression analysis and independent sample test. This study found that work context did not influence the level of auditor's concern to professional sanction but auditor's concern to professional sanction influences his or her independence to the audited. Finally, this research provides evidence that professionalism and concern to professional sanction have substitution effect to auditor’s independence. Abstrak: Skandal dalam audit telah memburuk kredibilitas profesi akuntansi. Rendahnya penegakan hukum dan struktur kepemilikan yang terkonsentrasi di Indonesia (La Porta et al, 1999; Siregar, 2006) telah menyebabkan independensi auditor yang lebih rendah. Penelitian ini menggunakan teori kognitif sosial dalam pemodelan. Berdasarkan teori kognitif sosial, penegakan hukum mempengaruhi kepedulian auditor terhadap sanksi profesional. Kemudian, perhatian terhadap sanksi profesional adalah kognitif yang memengaruhi independensi auditor. Tujuan dari penelitian ini adalah untuk menguji pengaruh konteks kerja terhadap tingkat perhatian auditor terhadap sanksi profesional, peran perhatian auditor terhadap sanksi profesional terhadap profesionalisme dan kemandiriannya. Berdasarkan survei berbasis skenario di Jakarta, Surabaya, Semarang, Denpasar, Yogyakarta, kami menerima 186 kuesioner yang memenuhi syarat (83 kuesioner dari auditor yang bekerja di kantor akuntan non big 4 dan 103 kuesioner dari auditor yang bekerja di 4 perusahaan besar). Penelitian ini menggunakan analisis regresi berganda dan uji sampel independen. Studi ini menemukan bahwa konteks kerja tidak mempengaruhi tingkat perhatian auditor terhadap sanksi profesional, tetapi perhatian auditor terhadap sanksi profesional mempengaruhi independensinya terhadap auditor yang diaudit. Akhirnya, penelitian ini memberikan bukti bahwa profesionalisme dan perhatian terhadap sanksi profesional memiliki efek substitusi terhadap independensi auditor.